(untitled) (Indian Journal of Animal Production and Management, 2015)
The data on production performance of 191 cows of 5/8 Gir crossbreds maintained at RCDP on Cattle, Rahuri were utilized for study. The least squares means of lactation milk yield (LMY), 300 days milk yield (300DMY), lactation length (LL) and dry period (DP) were worked out. The overall mean LMY, 300DMY, LL and DP were 2889.44 ± 67.68 kg, 2882.13 ± 58.34 kg, 302.86 ± 4.62 days and 98.42 ± 5.44 days respectively. The period of calving and season of calving had non-significant effects on all the traits under study. The lactation order had significant (P<0.01) influence on LMY and 300 DMY. The phenotypic and genetic correlations of LMY with 300DMY and LL and between 300DMY and LL were positive and significant.